(3efJNH ef (B( (3cJGH (B) (3GdfSHI Edi GdehGVY hGdHdOGfs - (3YHO Gddg Hf YHO Gddg Hf CMeO eNQeI, CHh eMeO , GdWjH HGeNQeI,J (B947 (3g` s
(3ChdgG (B:s
(3GdCShGfi HGdVe hSchf GdegedI haJM GdQGh Ke Cda hfhf fSHI Edi CShGf HdOI HUYjO eUQ s
(3BNQgG (B:s
(3abGd c CjgG GdBOei GdNWGA Edi Cjf hef Cjf ? abdJ GQOJ Cf CfXQ Edi Yeb gPG GdHMQ abGd di (B: (3hcja hgPG QLd ai GdHMQ efP KdGK eFI SfI de jHdZ bYQI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGefs
(3HgG fXGe GdJYbjHIs
(3HBNQgG aGFOI djSJ ef GdefJNHs
(3cJHJ Hbde eged GdfbW cKjQkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B94 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B45s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 - (3U (B192 s
Keywords: (3GdLZQGajG h GdHdOGfs